Databases and Information Systems 12th International Baltic Conference, DB&IS 2016, Riga, Latvia, July 4-6, 2016, Proceedings - Arnicans, Guntis; Arnicane, Vineta; Borzovs, Juris; Niedrite, Laila (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the 12th International Baltic Conference on Databases and Information Systems, DB&IS 2016, held in Riga, Latvia, in July 2016. The 25 revised full papers presented were carefully reviewed and selected from 62 submissions. The papers are organized in topical sections on ontology, conceptual modeling and databases; tools, technologies and languages for model-driven development; decision support systems and data mining; advanced systems and technologies; business process modeling and performance measurement; software testing and quality assurance; linguistic components of IS; information technology in teaching and learning.